Engaging Parents in Special Education: An Examination of Knowledge and Access to Resources. Issue 3 (27th May 2022) - Huscroft-D'Angelo, Jacqueline; Farley, Jennifer; Hurley, Kristin Duppong; Lambert, Matthew; Trout, Alexandra
ABSTRACT: Parental engagement in special education promotes positive student outcomes and parent-school relationships. In order to promote engagement, parents must possess a basic knowledge and understanding of special education processes and parent and student rights. Little is known regarding parental knowledge about special education or how they learn about and access information on the special education process. This exploratory study surveyed 133 parents of students with disabilities to identify how they received special education related information, specific information received or searched across primary special education topics, and their perceived current and retrospective understanding of these topics as well as how these may differ based on specific parent and special education status characteristics. Findings indicate that parents gain the majority of information from personal communication (i.e., conversations with special education teachers, other parents), often independently search out additional information on key aspects of special education, and feel most knowledgeable about Individualized Education Programs (IEPs) and least knowledgeable about the legal aspects of special education. Significant differences were noted on some family characteristics in areas of satisfaction with resources, overall special education knowledge, and ways in which parents obtain information (e.g., school or on their own). Limitations, implications, and future research are discussed.